2019
DOI: 10.1002/aenm.201901503
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Metal Boride Morphology via Anion for Efficient Water Oxidation

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/aenm.201901503. Oxygen EvolutionElectrochemical energy conversion and storage devices including metal-air batteries, regenerative fuel cells, and watersplitting cells are critical to satisfy the future energy demand of human society. Oxygen evolution reaction (OER) is the key reaction in these technologies and accounts for the major performance loss due to its sluggish kinetics. Precious metal-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 33 publications
1
77
0
Order By: Relevance
“…In addition to the above mentioned non‐noble‐metal‐based catalytic materials, other earth‐abundant metal‐based compounds such as borides,47,90,91 nitrides,48,49,92 cyanides,93 and chlorides,51 have also been proven to be efficient electrocatalysts for the OER. Recently, Nsanzimana et al highlighted an amorphous ternary metallic boride (Fe‐Co‐2.3Ni‐B) electrocatalyst synthesized via a facile chemical reduction strategy 90.…”
Section: Classification Of the Non‐noble‐metal‐based Oer Electrocatalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above mentioned non‐noble‐metal‐based catalytic materials, other earth‐abundant metal‐based compounds such as borides,47,90,91 nitrides,48,49,92 cyanides,93 and chlorides,51 have also been proven to be efficient electrocatalysts for the OER. Recently, Nsanzimana et al highlighted an amorphous ternary metallic boride (Fe‐Co‐2.3Ni‐B) electrocatalyst synthesized via a facile chemical reduction strategy 90.…”
Section: Classification Of the Non‐noble‐metal‐based Oer Electrocatalmentioning
confidence: 99%
“…For this reason, we put primary focus on these non‐noble‐metal‐based electrocatalysts in this review. To overcome the high overpotential of the OER, numerous non‐noble‐metal‐based electrocatalysts have been developed, including metals/alloys,23,24 oxides,25–31 hydroxides,32–37 chalcogenides,38–42 phosphides,5,43,44 phosphates/borates,19,45,46 borides,47 nitrites,48,49 and other compounds 50,51…”
Section: Introductionmentioning
confidence: 99%
“…Both the samples were annealed in N 2 gas at 600 °C to obtain pure crystalline phases. Wang and co‐workers performed chemical reduction in an ice bath, under Ar environment, and used different Co precursors (chloride, nitrate, acetate, sulfate) to control the morphology of the resultant Co–B catalyst. They observed that nitrate precursor suppressed the rapid reduction of Co ions, leading to formation of 2D nanosheets, while chloride precursor promoted fast reduction, leading to 3D nanoparticle formation.…”
Section: Synthesis Routes To Obtain Metal Boridesmentioning
confidence: 99%
“…In recent years, various transition metal (TM) phosphides, 10 oxides, 11 chalcogenides, 12 borides, 13 nitrides 14 and their composites 15 have emerged as effective OER catalysts. Among these cost-efficient catalysts, TM phosphides are regarded as catalysts with superior electrocatalytic activity and stability in alkaline media to effectively promote the OER process in terms of thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%